Differential expression of protein in muscle of rats treated with fluoride and exercise - Lombarte, Mercedes (2021)
Chronic ingestion of fluoride (F) has been reported to produce insulin resistance. Conversely, exercising (E) increases the peripheral response to insulin, enhancing the effect of the hormone on target tissues. Previous work has shown that E can reverse insulin resistance caused by ingesting F. Therefore, the objective of this work was: to study the pattern of protein expression in rats that reversed the insulin resistance induced by F when performing E. Healthy female Sprague-Dawley rats (50 days) were divided into 3 groups (n = 6 per group): Control: drinking water F 0 ppm, F: drinking water F 15ppm and FE: drinking water F 15ppm + E 30 min per day on a treadmill. The treatments were applied for 30 days, then the animals were euthanized and the gastrocnemius muscles were obtained for proteomic analysis. Proteins related to carbohydrate metabolism are less expressed in group F than in the control. In contrast, the decrease in carbohydrate metabolism proteins was not observed in rats treated with F and E. Conclusion: physical exercise reverts the resistance to insulin induced by fluoride counteracting fluoride effects on proteins related to carbohydrate metabolism.